Significance of P influx and Root Growth in P Acquisition at Different Growth Stages of Maize, Wheat and Groundnut Grown in a P-Deficient Alfisol - Samal, Satnam Singh, Bernd Steingrobe, Norbert Claassen, Pratapbhanu Singh Bhadoria, Debasmita (Journal of the Indian Society of Soil Science, 2019)
Crop species differ in their phosphorus (P) efficiency i.e. their ability to grow well in low P supplying soils. To test this hypothesis, field experiments were carried out in a low P soil to study P efficiency of wheat (Triticum aestium L.), maize (Zea mays L.) and groundnut (Arachis hypogaea L.) during the whole growing season and the possible reasons of variation in P efficiency of these crops. Treatments replicated four times consisted of P-0 (no P), P-50 (50 mg P kg-1 soil) and P-400 (400 mg P kg-1 soil). Four harvests were made to cover whole growing season of all the crops. At each harvest, different soil and plant parameters were determined. Plot size varied from 10 m2 for the first three harvests and 16 m2 for the last harvest (at maturity). Taking the relative yield as measure of P efficiency (expressed by the yield at P-0 relative to the yield at P-400), maize was most efficient, yielding more than 80%, followed by groundnut, 75%, and wheat, 65% of their maximum yields. Total P uptake of maize was twice to those of wheat and groundnut. The variation in uptake efficiency was not related to size of root systems but mainly to the P influx. At P-0, although the root system of groundnut was only 50% of that of wheat, P uptake was the same; and maize had the same root length as wheat but P uptake was twice. Wheat was of intermediate P efficiency during the whole growing season while maize was inefficient in early growth stages and very efficient later. In contrast, groundnut was very efficient at the beginning and less efficient later. The efficiency of wheat was mainly based on its root system whereas maize and groundnut relied on a large P influx. The P influx was the major factor determining differences in P efficiency among the species as well as for the same species during the growing season under field conditions. To separate the influence of root and soil properties, model calculation of P influx were carried out by employing the nutrient uptake model. Measured influx was much higher than the calculated influx at low P level. Sensitivity analysis shows that at low P level the CLi (initial soil solutions P concentration) was the most sensitive parameter for all the three crops. Among the physiological parameters Imax and Km was found to play negligible role in P uptake at low P level. But at higher P level (P-400) Imax was the most sensitive parameters followed by r0 for P uptake of three crop species. The higher measured than calculated influx indicated that plant possesses mechanisms that enhance P transport to the root from soil. Possible reason for this enhanced transport may be through root exudates that increase P solubility in the rhizosphere or mycorrhizae symbiosis.